GROWTH OF A ࢋࢀࢊ࡯ LAYER ON A SILICON SUBSTRATE AND STUDY OF THE ELECTROPHYSICAL PROPERTIES OF THE CREATED HETEROSTRUCTURE AND ITS EFFECT ON HUMIDITY (Universal International Scientific Journal, 2026)
This article is about semiconductor materials science, Si- The issues of creatingheterostructures based on a cadmium telluride film and obtaining contacts to the created system areconsidered. The morphology of the obtained coatings, the amount of elements in the coating, theirdistribution, and the size of polycrystalline particles were studied using modern devices. The change inthe voltage-ampere characteristics of the obtained structure depending on the moisture content wasstudied.
Keywords: materials science; semiconductor; fundamental